Tổng hợp và nghiên cứu tính chất và khảo sát khả năng thăng hoa một số pivalat đất hiếm - Nguyệt và cộng sự, Triệu Thị (Vietnam Journal of Chemistry, 2014)
Some complexes between rare-earth elements and pivalic acid Ln(Piv)3.HPiv (Ln: Sm, Gd, Ho, Yb; HPiv: pivalic acid) were synthesized and their sublimation ability  have been studied. The synthesized complexes were studied by IR, thermal analysis and mass-spectroscopy methods. The obtained results show that pivalates evaporate comparatively well. The thermal separation of the pivalates is supposed as follows: Ln(Piv)3.HPiv Ln(Piv)3 evaporate and separate